ANALISIS HUBUNGAN KEPESERTAAN KELUARGA BERENCANA PADA PASANGAN USIA SUBUR - Rafika Sari; Nirwan Nirwan; Anugrah Umar (Voice of Midwifery, 2022)
A Family planning is an effort to regulate the number and distance of desired children through several ways to prevent/delay pregnancy in the work area of ​​the Lamasi Health Center. Several factors are thought to affect the high level of Unmet Need for Family Planning, including education, knowledge and income. , education and income in family planning participation at PUS in the working area of ​​the Lamasi Health Center. This type of research is descriptive analytic research by analyzing the description of a study. The population of this study were all PUS in the working area of ​​the Lamasi Health Center. The sampling method in this study was purposive sampling with a sample size of 128 respondents in the working area of ​​the Lamasi Health Center. Data were collected by interview based on questionnaires and documentation. Data analysis using SPSS program. The test used to determine the existence of a relationship using the chi square test with the results of the study showed that there was a relationship between the level of education and family planning participation at PUS with a p value of 0.000 (< 0.05).